Life with dyslexia - Soon, Kim Choon (2014)
“Life with Dyslexia” is an interactive website which uses the platform of the web to raise the awareness of dyslexia. Its purpose is to educate and provide information to correct the misconceptions people have regarding dyslexia. Through game-based learning, it stimulates the cognitive processes that allow people to recognise the differences between right-brain and left-brain learners. “Life with Dyslexia” incorporates the rapidly expanding usage of social media, in order to reach a wider audience and create awareness of the subject.